(untitled) (Perner’s Contacts, 2006)
Firm Hangartner runs transports of semi-trailers and swap bodies from Lovosice to Hamburg Billwerder terminal. Kögel Company presented in year 2006 bulk cargo semi-trailer Mega MAXX for intermodal transport road/railroad. Semi-trailers and swap bodies must have on car frame longerons two beaded points on each side for catching by beam ties of reloading mechanism. Manipulation is vertical